Pengaruh Operasional UPT dan Pengembangan SDM terhadap Kesejahteraan Pegawai dalam Meningkatkan Daya Saing pada UPT Samudera Nizam Zachman Jakarta - Yani, Ari Soeti; Fauzi, Yoga (Universitas Batanghari Jambi, 2025)
This study aims to test and analyze the moderation of the operational system of UPT and HR development on employee welfare in increasing the competitiveness of Samudera Nizam Zachman Jakarta. The population in this study used a sample of 133 respondents who were employees and consumers of Samudera Nizam Zachman Jakarta. The data collection technique used simple random sampling. The data processing method in this study was using smartPLS with the aim of testing the hypothesis. The results of this study concluded that there was a positive and significant influence between the variables of competitiveness, operational UPT and HR development on employee welfare. The competitiveness variable was unable to moderate the influence of operational UPT and HR Development on employee welfare of Samudera Nizam Zachman Jakarta